Investing EFL Students’ Experiences with ELSA as a Digital Tool for Speaking Practice in Satun, Thailand: A Qualitative Study - Nasution, Nurpadillah; Siregar, Fatimah Sari (Journal of English Language and Education, 2025)
The process of learning English in Thailand faces several challenges. One of the aim problems is the lack of opportunities for student to practice speaking English in real situations. This study examines investing EFL students’ experiences with ELSA as digital tool for speaking practice. 20 three-grade in junior high school in Muslim Suksa School. The data collected through speaking test and interview.The result show many students agree about ELSA speak application because the application its effectiveness for them because can use everywhere. ELSA speak make the student more confidently. They can also find out how good their English-speaking skills are.The study concludes that students in Thailand enjoy using the Elsa application and they also have experience using the Elsa application.